Pilot-assisted non-cyclic prefixed SFBC-OFDM - REN Shu-bo; SHANG Yong; GUO Jun-qi; XIANG Hai-ge (Tongxin xuebao)
A pilot-assisted non-cyclic prefixed space-frequency block-coded orthogonal frequency division multiplexing （Non-CP SFBC-OFDM） system was proposed. Unlike in the traditional cyclic prefixed SFBC-OFDM system, the transmitted sequence of the proposed system was designed in the way that block-type pilot sequences and OFDM symbols derived from the SFBC scheme had been arranged alternately without any cyclic prefix （CP） before each OFDM symbol. Moreover, based on interference cancellation, a recursive algorithm of joint channel estimation and data detection was proposed for the corresponding receivers. Simulation results show that the proposed system based on the recursive algorithm achieves lower bit error rate （BER） and higher information data transmission rate than the traditional cyclic prefixed STBC-OFDM system with least square （LS） or iterative LS channel estimation algorithm.